2010
DOI: 10.1002/anie.200906648
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled TiO2 Nanocrystal Clusters for Selective Enrichment of Intact Phosphorylated Proteins

Abstract: Mesoporous oxides have been used for selective separation and adsorption of biomolecules. [1][2][3][4][5][6][7][8][9][10][11] Inorganic oxide materials such as silica can be synthesized into highly ordered mesoporous structures featuring high in-pore surface areas, narrow pore size distributions, adjustable pore sizes, and modifiable surface properties. [10,[12][13][14][15] Such unique properties favor the selective enrichment of proteins or peptides based on the size-exclusion mechanism. Classic mesoporous si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 138 publications
(123 citation statements)
references
References 41 publications
3
120
0
Order By: Relevance
“…During the initial adsorption process, ~30% of RhB was adsorbed by the silicatreated clusters, while only 20% of RhB could be adsorbed by the untreated clusters. We have pointed out previously that the silica coating and etching processes enhances the surface charge and water dispersity of such clusters [40], which is confirmed by these experiments. Without the silica coating/removing treatment, the calcined TiO 2 clusters are in the form of large aggregates and cannot be well dispersed in water even after 10 min of sonication, while the silicatreated clusters can be well dispersed in water.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…During the initial adsorption process, ~30% of RhB was adsorbed by the silicatreated clusters, while only 20% of RhB could be adsorbed by the untreated clusters. We have pointed out previously that the silica coating and etching processes enhances the surface charge and water dispersity of such clusters [40], which is confirmed by these experiments. Without the silica coating/removing treatment, the calcined TiO 2 clusters are in the form of large aggregates and cannot be well dispersed in water even after 10 min of sonication, while the silicatreated clusters can be well dispersed in water.…”
Section: Resultssupporting
confidence: 82%
“…Recently, we and other groups reported a general strategy for the fabrication of novel porous nanostructured materials based on the self-assembly of nanocrystals [38][39][40]. We have demonstrated that the as-prepared mesoporous nanocrystal clusters can be used for selective enrichment of peptides and proteins from complex biological samples [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10. Illustration of (a) the procedure for the fabrication of the mesoporous TiO2 nanocrystal clusters and (b) the selective enrichment process of phosphorylated proteins using the mesoporous TiO2 clusters and the elutes were analyzed by CE or MALDI-TOF MS [97].…”
Section: Specific Capture Of Post-translational Peptides and Proteinsmentioning
confidence: 99%
“…10, Lu et al [97] described the preparation self-assembled TiO 2 nanocrystal clusters with different averaged pore sizes of 2.3, 2.5 and 3.5 nm, and their application on selective enrichment of phosphorylated proteins from a mixed solution of three proteins (one phosphorylated ␤-casein, two non-phosphorylated horseradish peroxidase and ␤-lactoglobin). Only ␤-casein was detected by capillary electrophoresis with UV detection at 200 nm when using the mesoporous TiO 2 clusters.…”
Section: Specific Capture Of Post-translational Peptides and Proteinsmentioning
confidence: 99%